Genetic basis of supernumerary tooth - Kannan, Suhailiza; Yasmin, Sarliza (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2019)
Teeth are highly mineralised tissues located at the entrance of the alimentary tract in both invertebrates and vertebrates [1]. Teeth are the elements of dermal skeleton that are present in a wide range of jawed vertebrates [2]. Though the main function of teeth is in chewing food, yet, they are also associated with defence, display of dominance as well as in the vocalisation in humans [3]. The human dentition comprises 20 teeth in the primary dentition and 32 in the permanent dentition [4, 5, 6]. Tooth agenesis denotes missing tooth/teeth as a result of developmental failure that results in decreased number of normal complement in human dentition [7]. Conversely, a supernumerary tooth denotes any tooth or odontogenic structure that is formed from a tooth germ resulting in more than the usual number of any given region in a dental arch [4, 5, 6]. A search was made in databases using the keywords ‘supernumerary teeth, mouse, humans, genetics’. The articles collected were subjected to a systematic review to analyse the genetic basis of supernumerary teeth. Supernumerary teeth can be seen in many genetic disorders; but they are more common in syndromes like Gardner’s syndrome, cleft lip and palate and cleidocranial dysplasia (CCD) and less commonly seen in Fabry disease, Nance-Horan syndrome, Ellis-Van Creveld syndrome, Rubinstein-Taybi syndrome and trichorhinophalangeal syndrome [8]. Genetic entities that represent supernumerary teeth as a salient finding have been attributed to autosomal dominant inheritance, X chromosome inheritance and to both the inheritance patterns based on their locus heterogeneity [9]. Also, there are many reports supporting the theory of familial tendency to supernumerary teeth which were more evident in the relatives of the affected individuals [10]. Moreover, Seema Gupta and Praveen Kumar reported based on their study that in 8.6% of cases, there was a history of the same abnormality observed in other members of the family, which ascertained the hereditary nature of hyperdontia to occur [11].